Regulatory analysis of root architectural and anatomical adaptation to nitrate and ammonium in Brachypodium distachyon - Rouina, Hamid; Singh, Dilkaran; Arlt, Christopher; Malekian, Babak; Schreiber, Lukas; Stich, Benjamin; Marshall-Colon, Amy (Frontiers in Plant Science, 2025)
Plants deploy different strategies to optimize the nitrogen (N) uptake via roots, based on a complicated regulatory network that controls root phenotype and physiology. Here, we studied the response of root architecture to varying N applications in the model species Brachypodium distachyon. Using a combination of phenotypic and transcriptomic analyses, we examined how different forms and concentrations of ammonium and nitrate affect root growth, biomass allocation, and N uptake. N concentrations significantly influenced root traits such as root length, root hair development, and aerenchyma formation in response to nitrate and ammonium. Plants grown in ammonium conditions had thin but highly branched roots, whereas nitrate application resulted in shorter, thicker roots with denser root hair at higher nitrate concentrations. Furthermore, using co-expression network analysis, we identified an Atypical Aspartic Protease (APs) gene encoding an aspartyl protease family protein and a phosphoenolpyruvate carboxylase 1 (PEPC1) gene in Brachypodium as potential regulators. Both genes have previously not been associated with N-form-specific root architectural and anatomical adaptions in Brachypodium. APs expression showed a positive correlation with total root length and lateral root development, along with a negative correlation with root hair density. In contrast, PEPC1 exhibited positive correlations with cortex, stele, root cross-sectional areas, and root hair density, while showing a negative correlation with total root length. Our findings provide new insights into the molecular mechanisms underlying N-form-specific root adaptation and highlight the functional plasticity of root systems in response to environmental nutrient cues laying the groundwork for targeted manipulation of root traits in other crops.